Development of a Theoretically Grounded, Web-Based Intervention to Reduce Adolescent Driver Inattention. (August 2018) - McDonald, Catherine C.; Brawner, Bridgette M.; Fargo, Jamison; Swope, Jennifer; Sommers, Marilyn S.
Motor vehicle crashes are the leading cause of adolescent death. Inattention to the roadway contributes to crash risk and often results from distractions, such as cell phone calls, texting, and peer passengers. We report on the development of a web-based intervention based on the Theory of Planned Behavior that aims to reduce adolescent driver inattention ( Let's Choose Ourselves ). In Phase I, we collected qualitative and quantitative data on adolescents' attitudes, perceived behavioral control, and subjective norms about driver inattention through focus groups with newly licensed adolescent drivers. In Phase II, we developed the content in an e-learning delivery system, performed beta- and pilot testing, and made refinements. In Phase III, we conducted a randomized controlled trial to evaluate feasibility. The development of Let's Choose Ourselves provides information for school nurses regarding intervention development strategies as well as promotion of safe adolescent driving by reducing driver inattention.